Localized In Vivo Activation of a Photoactivatable Doxorubicin Prodrug in Deep Tumor Tissue. (6th March 2013) - Ibsen, Stuart; Zahavy, Eran; Wrasidlo, Wolf; Hayashi, Tomoko; Norton, John; Su, Yongxuan; Adams, Stephen; Esener, Sadik
Abstract Sparing sensitive healthy tissue from chemotherapy exposure is a critical challenge in the treatment of cancer. The work described here demonstrates the localized in vivo photoactivation of a new chemotherapy prodrug of doxorubicin (DOX). The DOX prodrug (DOX‐PCB) was 200 times less toxic than DOX and was designed to release pure DOX when exposed to 365 nm light. This wavelength was chosen because it had good tissue penetration through a 1 cm diameter tumor, but had very low skin penetration, due to melanin absorption, preventing uncontrolled activation from outside sources. The light was delivered specifically to the tumor tissue using a specialized fiber‐optic LED system. Pharmacokinetic studies showed that DOX‐PCB had an α circulation half‐life of 10 min which was comparable to that of DOX at 20 min. DOX‐PCB demonstrated resistance to metabolic cleavage ensuring that exposure to 365 nm light was the main mode of in vivo activation. Tissue extractions from tumors exposed to 365 nm light in vivo showed the presence of DOX‐PCB as well as activated DOX. The exposed tumors had six times more DOX concentration than nearby unexposed control tumors. This in vivo proof of concept demonstrates the first preferential activation of a photocleavable prodrug in deep tumor tissue.